BATAS TANGGUNG GUGAT PENGANGKUT APABILA TERJADI KECELAKAAN KAPAL DENGAN PENGGUNA JASA ANGKUTAN PERAIRAN SUNGAI MAHAKAM KALIMANTAN TIMUR - Stefanus Roy Hendrayanto, Dina Paramitha Hefni Putri dan (Universitas 17 Agustus 1945 Samarinda, 2018)
In 1935 ships-Ordinance has been determined on the requirements of thefeasibility of doing the cruise ship and the requirements in the form oflicenses issued by the Indonesian Bureau of Classification issued by thegovernment or cq Harbormaster and the Head Office of the Department ofTransportation. To and survived the voyage, the ship inland waters mustbe equipped with ship letters which is a guarantee for the feasibility of theship to sail in accordance with the requirements specified in theOrdinance of 1935 ships and inland vessels Ordinance 1927 and itsimplementation rules. A ship is said to worth screens for transportingpassengers and / or goods if it has a certificate of excellence. It ismentioned in Article 6 paragraph ( 1 ) and ( 3 ) ships Ordinance 1935. Inthe operation of inland water transport in particular freight , carriers andshippers generally have never made a carriage agreement in writing butmade verbally, and thus the rights and obligations of the parties is notreflected clearly impractica. In the event of an adverse event party shippermoney due to damage, reduced or loss of an item because of an error oromission of the carrier, the carrier usually fixed indemnify though not asbig as the real loss suffered. In terms of passenger transport (people), thecarrier is always considered to be responsible for the losses suffered bythe passenger if he were injured or died, without any obligation for thepassengers or their heirs to prove their right to compensation, just whenhe argues that he suffered injuries caused by transporting it. The newpresumption disappears if the carrier can prove that the loss occurredthrough no fault on his part or can not be avoided ( overmacht ) orbecause of his own fault passengers.